Of Great Apes and Magpies: Initiations into Animal Behaviour - Gisela Kaplan (Animals, 2020)
This paper presents three case studies of exceptional human encounters with animals. These particular examples were selected because they enabled analysis of the underlying reasons that led the human participants to respond in new ways to their animal counterparts. The question asked here is whether sudden insights into the needs and abilities of an animal arises purely from an anthropocentric position as empathy because of genetic closeness (e.g., chimpanzees) or is something else and whether new insights can be applied to other phylogenetic orders not close to us, e.g., birds, and change research questions and implicit prejudices and stereotypes. Particularly in avian species, phylogenetically distant from humans, the prejudices (anthroprocentric position) and the belief in human uniqueness (human exceptionalism) might be greater than in the reactions to primates. Interestingly, in studies of great apes, contradictory opinions and controversies about cognitive abilities, especially when compared with humans, tend to be pronounced. Species appropriateness in test designs are desirable present and future goals but here it is suggested how different experiences can also lead to different questions that explode the myth of human uniqueness and then arrive at entirely different and new results in cognitive and affective abilities of the species under investigation.